Integrative Approach to Internal and External Crisis Communications Management. Part 2 - T. I. Alifanova (Управленческие науки)
As noted in the first part of the paper in the extensive literature on crises and crisis management, it is possible to allocate two main directions: internal —  where the main attention is paid to technical and structural aspects and external — where the organization focuses on managing of stakeholders. Despite the fact that over past 20 years each of these directions has being developed to a large extent independently, it had been revealed that there were definite number of opportunities for their integration. Based on the results of research given in the extensive list of used literature, it will be shown how both of these perspectives can be combined into single integrated structure. At the same time the study of potential for synthesis of internal and external perspectives is going to be covered by time frame of three main crisis stages: pre-crisis prevention, crisis management and post-crisis outcomes, and term “crisis management” will reflect activities at these stages of organizational management in broadest sense.